ENTREPRENERURIAL INTENTION OF UNDERGRADUATED STUDENTS: GENDER PERSPECTIVES - Venny Soetedja (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to study the effect of entrepreneurial self-efficacy and locus of control towards entrepreneurial intention, besides that it also aims to further study the role of gender on the effect of entrepreneurial self-efficacy and locus of control toward entrepreneurial intention. Entrepreneurial intention to become an entrepreneur is very important for the Indonesian economy to increase the number of entrepreneurs in Indonesia. This research used quantitative methods. The test used SPSS with 200 undergraduated student respondents who were currently pursuing higher education majoring in business management and have gotten entrepreneurial learning during higher education. The study results yield that entrepreneurial self-efficacy and locus of control influenced entrepreneurial intention partially and simultaneusly. The result also indicated that gender affect the relationship between entrepreneurial self-efficacy and locus of control to entrepreneurial intention, this study demonstrated that the influence of entrepreneurial self-efficacy is greater on entrepreneurial intention for female compared to male. This result shows the importance of strive for improvement for the entrepreneurial self-efficacy and locus of control of the female gender to increase entrepreneurial intention, especially for female in Indonesia.